Geometric parameters of the lumbosacral spine in elite rowers - Ogurkowska, M. B.; Lewandowski, J.; Kawalek, K. (Medicina dello Sport, 2016)
BACKGROUND: The shape of the lumbar spine can change in result of high mechanical loads occurring in strength endurance-based sport disciplines, e.g. in rowing. Rowers are exposed to high loads due to the non-ergonomic strain occurring in their lumbar spines. The aim of this study was to evaluate the shape of the lumbosacral spine based on the analysis of geometric parameters in elite rowers. METHODS: The study group included elite Polish rowers - 20 men, aged 21-33 who had trained for 8-20 years. The comparison group included 20 men rowing recreationally, of similar age and with no lumbar disc pathologies. Computed tomography was performed for determining the geometric parameters of the spine. A tensometric electrogoniometer was used to measure the range of mobility. The results were statistically analyzed. RESULTS: In the group of elite rowers the mean Lumbar Lordosis Index value was 11±2.36% with the Whitman-Ferguson angle 46±1.6°. In the same group the mean lumbar lordosis angle was 43±1.92°. Hip joint flexors contracture and hypermobility of the lumbar spine in the horizontal plane were found. An asymmetry of the lumbar spine motion was shown in both frontal and transverse plane. CONCLUSIONS: Rowers presented much higher values describing lumbar lordosis in comparison with literature data. The differences in lumbar spine mobility are typical for chronic overuse changes. Rowing is a type of sport that strongly affects lumbar spine, and in long term, can lead to chronic overuse changes.